2020
DOI: 10.1088/2515-7620/ab7501
|View full text |Cite
|
Sign up to set email alerts
|

High correlation but high scale-dependent variance between satellite measured night lights and terrestrial exposure

Abstract: Exposure to artificial light at night (ALAN) is a significant factor in ecological and epidemiological research. Although levels of exposure are frequently estimated from satellite-based measurements of upward radiance, and the correlation between upward radiance and zenith sky brightness is established, the correlation between upward radiance and the biologically relevant exposure to light experienced from all directions on the ground has not been investigated. Because ground-based exposure to ALAN can depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…For example, recent research has demonstrated the influence of light at night at a coarse scale on mountain lion predation on mule deer [45]. Because irradiance from ALAN can vary orders of magnitude within several hundred meters [46], higherresolution data are needed to sort the influence of ALAN on many existing datasets containing ecological information. For example, the National Park Service has an extensive species monitoring program, the data from which are ideally suited for queries on the effects of ALAN on species distribution, co-occurrence, and abundance.…”
Section: Ecologymentioning
confidence: 99%
“…For example, recent research has demonstrated the influence of light at night at a coarse scale on mountain lion predation on mule deer [45]. Because irradiance from ALAN can vary orders of magnitude within several hundred meters [46], higherresolution data are needed to sort the influence of ALAN on many existing datasets containing ecological information. For example, the National Park Service has an extensive species monitoring program, the data from which are ideally suited for queries on the effects of ALAN on species distribution, co-occurrence, and abundance.…”
Section: Ecologymentioning
confidence: 99%
“…A valid option to quantify light pollution can be the merge of ground level measurements with aerial ones. In this context, some studies have identified a reasonable correlation for light imagery between ground and satellite measurements [162,163]. Another path to quantify light pollution can be found in analytical modelling methods of sky glow.…”
Section: Light Pollution: Quantification and Astronomical Implicationsmentioning
confidence: 99%
“…Night-time satellite data are limited in spatial, spectral and temporal resolution, but color imaging from the international space station ISS, airborne measurements, and particularly UAVs have the potential to fill the existing gaps in ALAN related biodiversity research (Bouroussis and Topalis, 2020;Levin et al, 2020;Sánchez de Miguel et al, 2021). A key component to improving the utility of these data would be research efforts that can translate what remotely sensed values could represent for conditions at ground level, where first steps have been taken but uncertainties remain high (Simons et al, 2020). Furthermore, there is an urgent need for stand-alone satellite missions focused on understanding light pollution and its effects on biodiversity (Barentine et al, 2021).…”
Section: Interdisciplinary Barriers To Measuring Nocturnal Lightmentioning
confidence: 99%